Multimodal Analysis of an English Textbook Used for EFL Young Learners - Jamilah, Sitti; Ismail, Nyak Mutia; Faizah, Cut (English Department, Universitas Negeri Surabaya, 2024)
This study aimed to discover the visual values—regarding interactive meaning—contained in the “My Next Words” English textbook and used at an international primary school in Banda Aceh, Indonesia using Kress and Van Leuween’s (2006) visual complementarity—only focusing on interactive meaning. This study employed a descriptive qualitative approach. The data were qualitative in the form of pictures in the textbook. The data were collected through a documentation procedure. From the findings, the interactive meaning found is as follows. primarily it uses long shots for most of the distance; second, it exclusively uses oblique views; and third, it shows both background-free and background-filled photographs. This outcome suggests that the pictures presented in this book are appropriate for the target audience, which is youngsters. For children to understand the concepts and messages presented in the textbook, their vision needs to be more distinct and clear. It is recommended that to produce more thorough and complex conclusions, future research should subcategorize the age in greater detail.